Potential of Wind Speed for Wind Power Generation In Perlis, Northern Malaysia - I. Daut I. Daut; M. Irwanto M. Irwanto; Suwarno Suwarno; Y.M. Irwan Y.M. Irwan; N. Gomesh N. Gomesh; N. S. Ahmad N. S. Ahmad (Universitas Ahmad Dahlan, 2011)
This paper presents an analysis of the wind speed characteristics in Perlis, Northern Malaysia for the year of 2006. The characteristics consist of daily, monthly and annual mean wind speed. The Weibull distribution function is applied to analyze the wind speed characteristics and used to calculate the wind power generation potential. Potential of wind power generation is observed and analyzed during 24 hours (9th March 2011). The analysis result of monthly mean wind power and energy density show that the early (January to march) and the end (December) of year have a high wind power and energy potential, but the middle of year they are very low, it is necessary to develop a special wind power generation capable of harnessing the little wind resource available in Perlis. Observation during 24 hours (9th March 2011), for a 24 V wind power generation gives 10% of its total output voltage.